Shelf life studies on Red Palm Oil - Archana U (Department of Home Science, College of Agriculture, 1999)
The study entitled "Shelf life studies on red palm oil" is a comprehensive study carried out with an objective to assess the qualitative changes of red palm oil during storage. Red palm oil is extracted from the mesocarp of oilpalm fruit which is deep red in colour due to its high